Unfitness to plead in England and Wales: Historical development and contemporary dilemmas - Brown, Penelope (Medicine, science, and the law, 2019)
Fitness to plead refers to a criminal defendant’s ability to participate at trial. The purpose of fitness-to-plead laws is to protect the rights of vulnerable individuals who are unable to defend themselves in court and to preserve natural justice in the legal system while balancing the needs to see …